Optimal outcomes : free yourself from conflict at work, at home, and in life - Goldman-Wetzler, Jennifer (Harper Business, an imprint of HarperCollinsPublishers, 2020)
A founding CEO and his top salesperson are engaged in a heated clash over her compensation package. A mother and daughter are locked in a nasty cycle of blame and attack. A high-profile executive team is struggling with aggressive political infighting. In all these cases, every effort to talk it out has been unsuccessful. Where can you turn when your attempts to resolve conflict fail? Most approaches emphasize collaboration. You are supposed to sit down, calmly talk through your differences, and find a solution. But what if nothing seems to work, no matter what you do? When situations resist resolution, the Optimal Outcomes Method teaches us conflict freedom. This innovative method, based on Dr. Jennifer Goldman-Wetzler<U+2019>s training at the Program on Negotiation at Harvard Law School, two decades as a consultant to Fortune 500 and high-growth CEOs and senior teams, grassroots work with Middle East leaders, US government-funded research on terrorism, and her popular course at Columbia University, Optimal Outcomes reveals eight groundbreaking practices proven to help people everywhere free themselves from conflict. With inspiring stories from clients, students, and Dr. Goldman-Wetzler<U+2019>s own life lighting the way, you<U+2019>ll learn to observe complex situations with clarity, access your shadow values (things you really care about but have been unwilling to admit), and take bold, simple, surprising action. Optimal Outcomes blends mindfulness, Jungian psychology, and practical, step-by-step advice to free anyone from seemingly impossible conflict. Applying the practices, you<U+2019>ll reach your Optimal Outcome<U+2014>which may be vastly different from what you originally imagined, but more satisfying than you ever dreamed possible.